2010
DOI: 10.1590/s1519-38292010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Mastectomy versus conservative surgical treatment: the impact on the quality of life of women with breast cancer

Abstract: OBJECTIVES: to compare the impact of mastectomy and conservative surgery on the quality of life of patients with breast cancer. METHODS: an assessment was made of the quality of life of patients undergoing mastectomy or segmentary mastectomy, at the Pouso Alegre Clinical Hospital, in the Brazilian State of Minas Gerais, using SF-36. The patients were grouped by age (<50 years and >50 years) and years of schooling (<8 years and >8 years). The Mann-Whitney test was used to compare the groups with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
1
13
1
11
Order By: Relevance
“…The chronic pain which appears after surgery is explained as the result of the injury to structures such as muscles and ligaments -and as neuropathic, when it affects nerves or is a dysfunction of the nervous system 6,8 . Therefore, when one evaluates the impact that these operations can have on the patients' quality of life, it is evidenced that the mastectomy can result in a lower score for quality of life, as the pain which can be caused by the surgery can lead to functional compromise 11 . 3 sought the characteristics of the pain, they identified that the women who undertake treatment for breast cancer report the pain as intermittent and constant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chronic pain which appears after surgery is explained as the result of the injury to structures such as muscles and ligaments -and as neuropathic, when it affects nerves or is a dysfunction of the nervous system 6,8 . Therefore, when one evaluates the impact that these operations can have on the patients' quality of life, it is evidenced that the mastectomy can result in a lower score for quality of life, as the pain which can be caused by the surgery can lead to functional compromise 11 . 3 sought the characteristics of the pain, they identified that the women who undertake treatment for breast cancer report the pain as intermittent and constant.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge about the pain relief measures is extremely important for the teams who work with these women 4,18 . Appropriate pain management must be implemented, avoiding self-treatment, since this can further compromise the symptom of pain in women with breast cancer 11,13 . …”
Section: Pain In Women With Breast Cancermentioning
confidence: 99%
“…18 They are the women of less social classes, numbers that remain on the rise, evidencing a process of feminization of poverty. In Brazil, many families are headed by women and the most of them live in the metropolitan areas.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study found that women who perform total mastectomy when compared to those who undergo Segmented mastectomy have a worse evaluation in this dimension. 18 In Nepal, women with breast cancer had good results in the Physical Functioning dimension, especially women with higher education level. In the Sexual Function and Sexual Pleasure, QOL losses were higher.…”
Section: Discussionmentioning
confidence: 99%
“…However, this step is important so there is value and improvement of quality of life and the self care, as discussed by some authors 5,6,23 . Being so, questions referring the shoulder functionality, to the impossibility to re-take the labor activity and the branch of acceptance of her mutilated body, propels reflective actions surrounding esthetic concepts (as shaving of the affected area and lymphedema) and new life styles (obstacles or physical restrictions).…”
Section: Discussionmentioning
confidence: 99%